2020
DOI: 10.5194/cp-16-953-2020
|View full text |Cite
|
Sign up to set email alerts
|

Stripping back the modern to reveal the Cenomanian–Turonian climate and temperature gradient underneath

Abstract: Abstract. During past geological times, the Earth experienced several intervals of global warmth, but their driving factors remain equivocal. A careful appraisal of the main processes controlling past warm events is essential to inform future climates and ultimately provide decision makers with a clear understanding of the processes at play in a warmer world. In this context, intervals of greenhouse climates, such as the thermal maximum of the Cenomanian–Turonian (∼94 Ma) during the Cretaceous Period, are of p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 126 publications
0
27
0
Order By: Relevance
“…One of the major challenges in the study of warm climate periods, for example, in the Cretaceous (e.g., Laugié et al., 2020; O'Brien et al., 2017; Tabor et al., 2016) or the early Eocene (e.g., Huber & Caballero, 2011; Lunt et al., 2012; Zhu et al., 2019), is the discrepancy between more strongly elevated global temperatures with low meridional gradients inferred from proxies and the conditions simulated by climate models (e.g., Huber, 2012; Upchurch et al., 2015). Challenges lie, for example, in the correct calibration and conversion of proxy data into local and global temperature estimates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the major challenges in the study of warm climate periods, for example, in the Cretaceous (e.g., Laugié et al., 2020; O'Brien et al., 2017; Tabor et al., 2016) or the early Eocene (e.g., Huber & Caballero, 2011; Lunt et al., 2012; Zhu et al., 2019), is the discrepancy between more strongly elevated global temperatures with low meridional gradients inferred from proxies and the conditions simulated by climate models (e.g., Huber, 2012; Upchurch et al., 2015). Challenges lie, for example, in the correct calibration and conversion of proxy data into local and global temperature estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Paleogeography was also identified as a major control of temperature gradients by Laugié et al (2020), who compiled proxy and climate model estimates of zonal mean temperatures for the Cenomanian-Turonian period (∼94 Ma). The gradients simulated here for this period fall within the range spanned by other models (Laugié et al, 2020), although some are closer to the lower gradients suggested by proxies (see supporting information section 7 and Figures S16a and b). At ∼125 Ma, simulated SST gradients compare well with those from Steinig et al (2020), who argue for an improved agreement with proxies when applying updated calibrations (also see Figures S16c and S16d).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulations are initialized with warm idealized conditions adapted from those described in Lunt et al (2017). The constant initial salinity field is set to 34.7 PSU, and ocean temperatures are initialized with the depth-dependent distribution of Laugié et al (2020).…”
Section: Boundary and Initial Conditionsmentioning
confidence: 99%
“…This Earth system model coupled the Laboratoire de Météorologie Dynamique zoom (LMDZ5) atmospheric model (3.75 × 1.875 • in longitude-latitude, 39 vertical levels) (Hourdin et al, 2013) and Organising Carbon and Hydrology In Dynamic Ecosystems (ORCHIDEE) land surface model (Krinner et al, 2005) with the Nucleus for European Modelling of the Ocean (NEMO) , which includes ocean and sea-ice dynamics (2 • resolution and 31 vertical levels in the ocean), together with the marine biogeochemical model PISCES (Aumont et al, 2015). IPSL-CM5A has been used for several paleoclimate studies (e.g., Kageyama et al, 2013;Roberts et al, 2014;Tan et al, 2017;Zhuang and Giardino, 2012), including studies benefiting from the explicit representation of marine biogeochemistry (Bopp et al, 2017;Ladant et al, 2018;Le Mézo et al, 2017), vegetation dynamics and land biosphere (Tan et al, 2017). Still, IPSL-CM5A computation time, which averages 10 SYPD, has hindered its use for multi-millennial experiments that are typical for Quaternary or "deep-time" paleoclimate studies in which a fully equilibrated deep ocean is mandatory.…”
Section: Introductionmentioning
confidence: 99%